Molecular dynamics simulation of hyaluronic acid hydrogels: Effect of water content on mechanical and tribological properties. (November 2022) - Wu, Yuyao; Wang, Fei; Shi, Yanbin; Lin, Guimei; Qiao, Jinwei; Wang, Li
Highlights: The atomic models with different water content of hyaluronic acid hydrogel were established, and the mechanical parameters of each model were analyzed in detail. Under the condition of continuous compression, the atomic space distribution of the hydrogel model with different water content was analyzed in detail. The friction forces of different water content models under different sliding friction speeds and different loads are simulated in detail. In the way of simulation, the general trend of hydrogel mechanics and wear resistance with water content was obtained. Abstract: Background and objective: Recently conducted biomedical studies have shown that the drug diffusivity of hyaluronic acid hydrogel plays an important role in the treatment of joint diseases. The drug diffusivity is closely related to the water content of hydrogel. In addition, different water content will not only affect its mechanical and tribological properties, but also change the effect of drug release. Methods: In this work, a Molecular dynamics simulation was used to investigate the effect of water content on spatial distribution, tribological and mechanical properties of a hyaluronic acid hydrogel network. This paper focuses on the analysis and calculation of the radial distribution function of 20, 40, 60, and 80% water content model and the friction force and mechanical parameters under the influence of different load and friction speed. Results: The results show that at 20 and 40% water content, the spatial distribution is loose and the intermolecular force is not strong, resulting in a major lack in tribological and mechanical properties; whereas at 60 and 80% water content, the spatial distribution becomes gradually compact and the intermolecular force is gradually increased. The tribological and mechanical properties manifest a marked improvement. Conclusions: The calculations reveal that the hydrogel model has the best wear resistance, pressure resistance, and plastic deformation resistance at 80% water content. In the range of 20–80% water content, the mechanical properties and friction properties of hydrogels become better and better with the increase of water content.